USING VIDEO ANIMATION IN CONTEXTUAL TEACHING AND LEARNING TO ENHANCE STUDENT ENGAGEMENT IN SCIENCE LEARNING - Eka Puspitasari; Wawan Krismanto; Ritha Tuken; Yonathan S. Pasinggi (Universitas Lambung Mangkurat, 2024)
Science learning that only prioritizes conceptual learning and ignores relevance to the environmental context and society in which students live needs to be immediately abandoned and changed to contextual learning oriented towards student activity and engagement. The research aims to implement the contextual teaching and learning (CTL) model assisted by video animation to improve student learning processes and engagement in science learning about the Water Cycle. For this reason, a qualitative approach to this type of classroom action research is a research method that is considered relevant. Class actions were carried out in cycles (planning, implementation, observation and reflection) in class 5 of SDN 3 Watang Sidenreng, Sidrap Regency, South Sulawesi. Three instruments were used as data collection tools: teacher and student observation sheets and student learning engagement observation. Descriptive analysis was used for the analysis of data. The result is significant changes after implementing three class actions, especially in the student-centred orientation of learning science. With worksheets supported by animated video media, everything strengthens the contextualization of the Water Cycle material to be closer to students' daily phenomena. Various activities and learning experiences are realized when implementing the CTL model's seven learning steps (syntax). At the end of the cycle, student engagement could increase significantly. Thus, implementing CTL assisted by video animation could improve the learning process and engagement.